Reformasi sufistik : "halaman akhir" Fikri Yathir - Rakhmat, Jalaluddin, 1949- (Bandung : Pustaka Hidayah, 1998)
Sufism, Indonesia; articles previously published in Ummat magazine.
Includes index.
Keywords: Sufism -- Indonesia